University Students’ Perceptions toward ChatGPT as English Learning Tool - Arumsari, Arumsari; Pravitasari, Suryanti Galuh; Octaviani, Saly Kurnia; Satrionugroho, Bambang (Universitas Pahlawan Tuanku Tambusai, 2025)
ChatGPT offers the convenience of translating text from English to Indonesian and vice versa. This feature is highly utilized by students, helping them find meanings and translate sentences. For college students from engineering faculty, this technology can ease them to learn English and help them to do English tasks. This study will examine college students' perceptions of English language learning using Chat GPT. This research applied a qualitative approach to determine students' perceptions of the use of GPT chat media to improve their English language skills. This research used interviews, observations, questionnaires to collect data from respondents. This research concluded that students believe that ChatGPT has positive impact on facilitating information access and assisting students' English coursework